Makna dan Simbol pada Tembang Upacara Siraman Adat Sunda sebagai Usulan Bahan Ajar Teks Deskripsi di Kelas VII SMP - Wachyudin Wachyudin; Desita Nurama Ningsih; Nira Wahyuni (Badan Pengembangan dan Pembinaan Bahasa, 2025)
This study aims to describe the form, meaning, and symbols contained in the Sundanese traditional siraman ceremony songs, and propose their use as teaching materials for descriptive texts in grade VII of junior high school. This study uses a qualitative method with Charles Sanders Peirce's semiotic approach to interpret the representamen, objects, and interpretants of each song. The analysis results show that the songs contain messages of affection, parental approval, self-reflection, responsibility, and prayers for blessings for the bride and groom. Cultural symbols such as water, flowers, candles, and sinjang kebat enrich the meaning of the siraman tradition as a process of purification and moral strengthening. The research findings are then adapted into proposed teaching materials for descriptive texts based on local culture that are in accordance with the Merdeka Curriculum, so as to improve descriptive literacy skills while fostering students' appreciation of Sundanese culture. This study contributes in the form of integrating local traditions in Indonesian language learning through the development of contextual and culturally valuable materials. Abstrak Penelitian ini bertujuan untuk mendeskripsikan bentuk, makna, serta simbol-simbol yang terkandung dalam tembang upacara siraman adat Sunda, serta mengusulkan pemanfaatannya sebagai bahan ajar teks deskripsi di kelas VII SMP. Penelitian ini menggunakan metode kualitatif dengan pendekatan semiotika Charles Sanders Peirce untuk menafsirkan representamen, objek, dan interpretan dari setiap tembang. Hasil analisis menunjukkan bahwa tembang-tembang tersebut mengandung pesan kasih sayang, keridaan orang tua, refleksi diri, tanggung jawab, serta doa keberkahan bagi calon pengantin. Simbol-simbol budaya seperti air, bunga, lilin, dan sinjang kebat memperkaya makna tradisi siraman sebagai proses penyucian dan peneguhan moral. Temuan penelitian kemudian diadaptasi menjadi usulan bahan ajar teks deskripsi berbasis budaya lokal yang sesuai dengan Kurikulum Merdeka, sehingga mampu meningkatkan kemampuan literasi deskriptif sekaligus menumbuhkan apresiasi siswa terhadap budaya Sunda. Penelitian ini memberikan kontribusi berupa integrasi tradisi lokal dalam pembelajaran bahasa Indonesia melalui pengembangan materi yang kontekstual dan bernilai kultural.